2008
DOI: 10.2165/00002018-200831090-00005
|View full text |Cite
|
Sign up to set email alerts
|

Inhaled Corticosteroids and Adrenal Insufficiency

Abstract: The results of this study confirm the occurrence of adrenal insufficiency in patients treated with ICS. Although the prevalence of ICS-induced AI reported in this study is low, the likelihood of under-diagnosis underlines the need to consider this risk in patients when prescribing these drugs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(39 citation statements)
references
References 18 publications
0
39
0
Order By: Relevance
“…This may be linked to differences in the active substances and/or pharmacodynamic properties related to administration mode; oral administration being generally associated with slower absorption/distribution, higher metabolism due to hepatic first-pass effect, and lower biologically active circulating metabolites. Adrenal insufficiency and Cushing's syndrome have also been reported in patients treated with inhaled CS (Molimard et al, 2008). In our study, however, the small number of subjects taking CS using either mode did not allow us to examine the effect of administration method.…”
Section: Cs Use and Cognitive Declinementioning
confidence: 65%
“…This may be linked to differences in the active substances and/or pharmacodynamic properties related to administration mode; oral administration being generally associated with slower absorption/distribution, higher metabolism due to hepatic first-pass effect, and lower biologically active circulating metabolites. Adrenal insufficiency and Cushing's syndrome have also been reported in patients treated with inhaled CS (Molimard et al, 2008). In our study, however, the small number of subjects taking CS using either mode did not allow us to examine the effect of administration method.…”
Section: Cs Use and Cognitive Declinementioning
confidence: 65%
“…Dinsen et al [4] reviewed this topic and concluded that oral glucocorticoids could induce adrenocortical insufficiency in up to 46-100% of patients. Even inhaled glucocorticoid treatment can lead to adrenocortical insufficiency [14,15,16]. Only few results of adrenocortical function in relation to intermittent glucocorticoid pulse therapy have been reported [17,18,19].…”
Section: Discussionmentioning
confidence: 99%
“…Potential systemic side effects of ICSs include suppression of the hypothalamus-pituitaryadrenal (HPA) axis, Cushing syndrome, osteoporosis, cataracts, dermal thinning and bruising, adrenal insufficiency, and growth suppression in children (4,5). Cushing syndrome and associated adrenal insufficiency have been reported with high doses of ICSs or as a result of drug interaction with CYP3A4 inhibitors (64,65). Additionally, ICS therapy increases the risk of pneumonia in patients with COPD (6,55).…”
Section: Adverse Effectsmentioning
confidence: 99%
“…They are all extensively metabolized by intestinal and hepatic CYP 3A4, which affects their systemic availability and clearance. Adrenal suppression, Cushing syndrome, and death have been reported with coadministration of these agents (64,74).…”
Section: Drug Interactionsmentioning
confidence: 99%